Unlearning (Un)Located Ideas in the Provincialization of Urban Theory. Issue 9 (1st September 2016) - Lawhon, Mary; Silver, Jonathan; Ernstson, Henrik; Pierce, Joseph
Abstract : Lawhon M., Silver J., Ernstson H. and Pierce J. Unlearning (un)located ideas in the provincialization of urban theory, Regional Studies . Postcolonial scholars have argued for the provincialization of urban knowledge, but doing so remains an opaque process. This paper argues that explicit attention to 'learning to unlearn' unstated theoretical assumptions and normativities can aid in provincialization, and demonstrate ways in which theorizing entails a socio-spatial situation. The authors' efforts to grapple with operationalizing learning to unlearn in three different urban cases are described, followed by an articulation of strategies for theorizing which more explicitly acknowledge theory-building's situatedness as well as points of reflection for developing postcolonial urban theory. It is argued that this usefully shifts the focus of unlearning from 'who' is theorizing 'where' towards theory's unstated norms and assumptions.